Epidemiological and biological characteristics of IncR plasmids as multihost antibiotic resistance carriers - Zhang, Duo; Li, Shuang; Zhang, Xindan; Zheng, Shuai; Zhou, Di; Hou, Qinlong; Li, Gen; Han, Huiming (Frontiers in Microbiology, 2025)
IncR plasmids are important resistance vectors broadly disseminated among various Gram-negative bacteria. Their capacity for inter-host transmission facilitates the spread of antimicrobial resistance genes across diverse ecological systems, posing a significant threat to global public health. Since their initial identification in 2006 within the multidrug-resistant plasmid pK245 from Klebsiella pneumoniae, research on the physiological features, epidemiological characteristics, and specific role of IncR plasmids in resistance dissemination has remained limited and fragmented. To address this gap, the present review systematically examines current literature on IncR plasmids, focusing on their host range, resistance gene composition, coexistence with transposable elements and insertion sequences, and their co-integration with other plasmids (e.g., IncF and IncX3), which often leads to the formation of co-linear plasmids. Available evidence indicates that IncR plasmids are predominantly found in Enterobacteriaceae (e.g., Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae, Salmonella spp.) and to a lesser extent in non-fermenters such as Pseudomonas aeruginosa. Despite their low copy number, which minimizes the metabolic burden on the host, IncR plasmids demonstrate high stability and retention within bacterial populations, enabling their long-term persistence and global dissemination. In recent years, IncR-carrying strains have been increasingly identified in isolates from human, animal, and environmental sources. Moreover, their co-integration with other resistance plasmids may further expand their resistance spectrum and host range, presenting a growing challenge to clinical antimicrobial therapy. This review aims to summarize the key genetic features and transmission dynamics of IncR plasmids, providing theoretical insights for the control of their global dissemination and guidance for future research into their resistance mechanisms and evolutionary trajectories.